Pengaruh harga sukuk negara ritel seri sr-005, tingkat inflasi dan bi rate terhadap tingkat permintaan sukuk negara ritel seri sr-005 - Faizul Rahman; Ardi Paminto; Maryam Nadir (JURNAL MANAJEMEN, 2016)
This study aimed to analyze the effect of retail state sukuk price SR-005, inflation and BI rate on the demand of retail state sukuk SR-005. The population in this study is a retail state sukuk SR-005. The samples in this study used saturated samples, and the samples obtained were market price data and the monthly sales volume of retail state sukuk SR-005 for the period March 2013 to February 2016. The analysis tool used was multiple linear regression analysis. The results shows that the price of retail state sukuk SR-005 variable and the inflation rate variable effect negatively on the demand of retail state sukuk SR-005 but it’s not significant. While the variable of BI rate effects negatively and significantly on demand of retail state sukuk SR-005.Keyword: Retail state sukuk prices SR-005, the inflation rate, the BI rate and demand of the retail state sukuk.